La stiva e l’abisso di Michele Mari. Romanzo fra favola e metanarrazione - Janusz, Joanna (Romanica Silesiana, 2020)
From the moment of his literary debut in 1989, Michele Mari is considered to be the representative of classic tendencies in contemporary Italian literature. One of the most noticeable characteristics of his writing is the presence of autobiographic elements which appear in all his works with different intensity, but also the archaization of style and language, literary references and metaliterary reflexions. This article aims at showing how the 1992 novel La stiva e l’abisso connects two of those aspects of Mari’s writing: intertextuality and literary references to adventure novel genre, as well as it reflects on the role and value of the literature for the contemporary people. It analyses basic narrative instances, that is the narrator, narrative structure, place and time of events, in order to show how they result in metaliterary reflexion.